Relación entre estilo de aprendizaje y rendimiento académico en estudiantes de farmacia de la Universidad de Costa Rica - Lizano Barrantes, Catalina (2015)
Learning styles can be defined as the set of features that characterize the way people learn and process information. The aim of this study is to establish the relationship between learning styles and academic performance of students who completed the fifth year of the Pharmacy Program at Universidad de Costa Rica during the years 2011 to 2013. We applied the Honey-Alonso Learning Styles questionnaire. Regarding the overall mean, we obtained that there are no differences in the preference for an active, reflective, theoretical or pragmatic style. Students don’t have a pure learning style, but a combination of two or more of them, which favours the learning process as they have more tools to adapt to the teachers’, the courses’ and the study program’s requirements.